2013
DOI: 10.1186/1423-0127-20-72
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs have a sex-specific association with metabolic syndrome

Abstract: BackgroundThe microRNAs let-7 g and miR-221 have been demonstrated to be related to the glucose metabolism. This study assessed the serum levels of these two microRNAs in subjects with and without metabolic syndrome (MetS).ResultsThe serum microRNA levels were detected in 102 subjects aged 40 to 80 years who were recruited from the general population. The status of MetS was defined by the Adult Treatment Panel III (ATP III) criteria modified for Asians. Subjects with histories of cardiovascular diseases or who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 36 publications
0
90
0
1
Order By: Relevance
“…Targets IRS2 in liver cells and macrophages [19] miR-33a, miR-33b elevated in the serum of an Asian cohort with MetS (Table 2, row I) [37]. Levels of both miRNAs increased in parallel with increasing number of MetS components presented.…”
Section: _ T D $ D I F F ] Refsmentioning
confidence: 96%
See 1 more Smart Citation
“…Targets IRS2 in liver cells and macrophages [19] miR-33a, miR-33b elevated in the serum of an Asian cohort with MetS (Table 2, row I) [37]. Levels of both miRNAs increased in parallel with increasing number of MetS components presented.…”
Section: _ T D $ D I F F ] Refsmentioning
confidence: 96%
“…For individuals presenting with four to five components of MetS, let-7 g and miR-122 were both significantly increased. Moreover, the elevation of serum let-7 g was significantly associated with a low level of HDL-cholesterol and high blood pressure [37]. miR-122 has been shown to regulate FA metabolism, cholesterol synthesis, and cholesterol levels [38].…”
Section: _ T D $ D I F F ] Refsmentioning
confidence: 99%
“…It has been shown that miR-103, miR-107, and miR-33 regulated insulin sensitivity and glucose homeostasis [175À177]. Two circulating miRNAs (let-7 g and miR-221) have a female-specific elevation in individuals with MS [178]. Concerning the features of MS, blood miR-197, miR-23, and miR-509-5p positively correlated with BMI, and elevated circulating miR-130a and miR-195 were associated with high BP [179].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…miRNAs can be exported or released by cells and circulate with the blood in a remarkably stable form by packaging into microparticles, e.g., exosomes, microvesicles, or apoptotic bodies (4, 5), binding to RNA-binding proteins or high-density lipoprotein (68). Although the precise role of circulating miRNAs is still largely unknown, dysregulated expression of circulating miRNAs has been found to be associated with the occurrence of a variety of diseases including cancers (8, 9, 914), cardiovascular disease (1520), diabetes mellitus (21), obesity (22, 23), neurodegenerative disease (24, 25), and autoimmune disease (26), as well as altered physiological states such as pregnancy (27). Thus, circulating miRNAs have become of increasing interest as non-invasive biomarkers for predicting disease risk and prognosis, as well as for cancer early diagnosis and monitoring of treatment responses.…”
Section: Introductionmentioning
confidence: 99%